(untitled) (Oil and Gas Engineering, 2017)
The article analyzes the problems of hydrate formation, which arise in the process of extraction, preparation and transport of gas. The possibility of using a new reagent «RENA-Crystal», as an additive to methanol to prevent hydrate formation in the gas condensate fields. The results of the calculation antigidratnyh properties of «RENA-Crystal». According to the results of industrial tests demonstrated the effectiveness of using a new inhibitor for the prevention of hydrate formation in the training system to Yablunivska comprehensive gas treatment unit. industrial test results confirmed the effectiveness of the «RENA-Crystal» to prevent the formation of hydrates. Keywords: hydrate inhibitor, methanol, gasindustrial equipment, efficiency of use.